2016
DOI: 10.1093/icvts/ivw064
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for primary pulmonary lymphoepithelioma-like carcinoma

Abstract: Primary lung LELC is closely associated with Epstein-Bar virus infection but not involved in EGFR mutation pathway. Radical surgery could achieve a good outcome for resectable pulmonary LELC, and regional lymph node status is a vital prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
52
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 10 publications
15
52
2
Order By: Relevance
“…Similar to a report from Lin et al, adjuvant chemotherapy after radical dissection did not improve DFS and OS in our study (23). However, in other larger cohort, postoperative adjuvant chemotherapy could prolong OS of patients with stage IIIa cancer (2).…”
Section: Discussionsupporting
confidence: 89%
“…Similar to a report from Lin et al, adjuvant chemotherapy after radical dissection did not improve DFS and OS in our study (23). However, in other larger cohort, postoperative adjuvant chemotherapy could prolong OS of patients with stage IIIa cancer (2).…”
Section: Discussionsupporting
confidence: 89%
“…In contrast with other subtypes of lung cancer, all results showed that LELC of the lung had a better prognosis 3, 6, 7, 8. Similarly, the above tendency was also obtained from our study.…”
Section: Discussionsupporting
confidence: 87%
“…Pulmonary lymphoepithelioma-like carcinoma is a rare and distinct subtype of non-small-cell lung cancer with an incidence of~0.7% of all non-small cell lung cancer cases. Pulmonary lymphoepithelioma-like carcinoma tends to affect young, non-smoking patients of Asian ethnicity [3][4][5][6][7][8][9]. It was previously classified as a variant of large cell carcinoma [10] but has recently been reclassified under other and unclassified carcinomas in the 2015 World Health Organization (WHO) classification of lung tumors [11].…”
Section: Introductionmentioning
confidence: 99%
“…Since most patients are diagnosed at an early stage, the prognosis for pulmonary lymphoepithelioma-like carcinoma patients is more favorable compared with other types of lung cancer, with a median overall survival of about 107 months vs. 13 months for non-pulmonary lymphoepithelioma-like carcinoma patients and a 5-year survival of about 60% [5,7]. The main treatment strategy for earlystage disease is surgery [3,6,7]. Unresectable patients often undergo multimodal therapy, primarily consisting of chemotherapy and radiotherapy with better prognosis than other types of non-small-cell lung cancer [19].…”
Section: Introductionmentioning
confidence: 99%